Programmable logic controllers principles and applications - Webb, John W (Prentice Hall, 1999)
Useful for an undergraduate-level course on PLCs or Electronic Controls, this book provides coverage on programmable logic controllers. It discusses applications for each PLC function, and includes an array of examples and problems that help students achieve an understanding of PLCs.